RESPON PERTUMBUHAN DAN HASIL TANAMAN CABAI MERAH KERITING (Capsicum annum Var. Longun L.) TERHADAP PEMBERIAN DOSIS PUPUK NPK DAN BOKASHI - Nurul Laili, Faiftin; Kurniastuti, Tri; Puspitorini, Palupi (Universitas Islam Balitar, 2020)
The aims of this study was 1) to determine the effect of interactions between the dose of NPK fertilizer and bokashi fertilizer on growth and yield of curly red chilli plants 2) to determine the effect of NPK fertilizer dose on the growth and yield of curly red chili plants 3) to determine the effect of bokashi fertilizer dose on the growth and yield of curly red chilli plants. This study was arranged using a factorial randomized block design (RAK), factor I was NPK fertilizer namely N1: 0.624 gram, N2: 0.832 gram, N3: 1.04 gram, N4 1,248 gram, factor II is fertilizer Bokashi is B1: 20.8 grams, B2: 41.6 grams, B3: 49.9 grams, B4: 62.4 grams. There were 16 treatments and repeated 3 times, so there were 48 experimental units. Data were analyzed by analysis of variance method based on (ANNOVA) level of 5% analysis of variance analysis. If the treatment has a significant effect on the observed variables then continued with the Duncan test of the level of 5%. The results of variance showed that there was a significant interaction with NPK fertilizer treatment (N) and Bokashi fertilizer (B) on plant height, stem diameter, number of leaves, anditotal number of fruit plantations at 14, 21, 28, 35, and 49 DAP (date after plant). The best treatment wasifound in the dosage of 0.832 gram NPK fertilizer and 41.6 gram Bokashi fertilizer (N2B2).